Hydration status and fluid balance of elite European youth soccer players during consecutive training sessions - Phillips, S. M.; Sykes, D.; Gibson, N. (Journal of Sports Science & Medicine, 2014)
The objective of the study was to investigate the hydration status and fluid balance of elite European youth soccer players during three consecutive training sessions. Fourteen males (age 16.9 +/- 0.8 years, height 1.79 +/- 0.06 m, body mass (BM) 70.6 +/- 5.0 kg) had their hydration status assessed from first morning urine samples (baseline) and pre- and post-training using urine specif-ic gravity (USG) measures, and their fluid balance calculated from pre- to post-training BM change, corrected for fluid intake and urine output. Most participants were hypohydrated upon waking (USG >1.020; 77% on days 1 and 3, and 62% on day 2). There was no significant difference between first morning and pre-training USG (p = 0.11) and no influence of training session (p = 0.34) or time (pre- vs. post-training; p = 0.16) on USG. Significant BM loss occurred in sessions 1-3 (0.69 +/- .22, 0.42 +/- 0.25, and 0.38 +/- 0.30 kg respectively, p < 0.05). Mean fluid intake in sessions 1-3 was 425 +/- 185, 355 +/- 161, and 247 +/- 157 ml, respectively (p < 0.05). Participants replaced on average 71.3 +/- 64.1% (range 0-36.6) of fluid losses across the three sessions. Body mass loss, fluid intake, and USG measures showed large inter-individual variation. Elite young European soccer players likely wake and present for training hypohydrated, when a USG threshold of 1.020 is applied. When training in a cool environment with ad libitum access to fluid, replacing ~71% of sweat losses results in minimal hypohydration (<1% BM). Consumption of fluid ad libitum throughout training appears to prevent excessive (.2% BM) dehydration, as advised by current fluid intake guidelines. Current fluid intake guide-lines appear applicable for elite European youth soccer players training in a cool environment.